TELAAH RELEVANSI PEMIKIRAN FAZLUL RAHMAN DAN SEKOLAH ISLAM TERPADU - Wiga Ananda; Thayyibi, Muhammad Ilham (An-Nahdlah: Jurnal Pendidikan Islam, 2024)
Islamic religious education should not only be a process of transmitting material, but far from that, it should be integrated into the personality and become a guide in daily activities. Fazlur Rahman is one of the Muslim scholars wrote his thoughts on the modernity of Islamic education. His ideas include the basis of Islamic education, namely the Al-Qur'an and Sunnah, the aim of Islamic education is to form a morally and intellectually complete human being, the education system integrates general knowledge and religion. Educational curriculum with a double movement and language mastery. The writing method is descriptive analysis with a library research approach. Analyze data collected through books or scientific journals, then describe it. The results of his research are that Fazlur Rahman's thoughts have relevance to Integrated Islamic Schools (SIT) which use integrated learning methods. The relevance of Fazlur Rahman's thoughts to SIT is a modern education system using strong Islamic idealism, a solution to the dualism of the education system with the integration of Islamic knowledge and general science, education based on the Qur'an and Sunnah and the formation of a critical, creative personality, able to analyze various things. problems and solutions, and whole physically, aqliyah and spiritually